2010
DOI: 10.1007/s00198-010-1447-3
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effects of pulsed electromagnetic fields on diabetic bone loss in streptozotocin-treated rats

Abstract: The results demonstrated that PEMF could partially prevent DM-induced bone strength and architecture deterioration and improve the impaired bone formation. PEMF might become a potential additive method for inhibiting diabetic osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 43 publications
5
63
1
Order By: Relevance
“…This mechanism may be responsible, at least in part, for the effect of magnetic fields on calcium ions in beta cells. Changes were greater, and reversibility lower, with square than with sinusoidal waves (15). A comparison of 10 Hz and 100 Hz PEMF soon after diabetic peripheral neuropathy treatment showed that the lower frequency was more effective (16).…”
Section: Discussionmentioning
confidence: 91%
“…This mechanism may be responsible, at least in part, for the effect of magnetic fields on calcium ions in beta cells. Changes were greater, and reversibility lower, with square than with sinusoidal waves (15). A comparison of 10 Hz and 100 Hz PEMF soon after diabetic peripheral neuropathy treatment showed that the lower frequency was more effective (16).…”
Section: Discussionmentioning
confidence: 91%
“…Bassett et al for the first time found that PEMF treatment, a more accessible and affordable non-contact modality, was able to dramatically accelerate fracture healing in patients [12]. Numerous studies have further proved that PEMF could promote potently osteogenesis and enhance bone mineralization both in vivo and in vitro [15], [16], [47]. Clinical investigations revealed that PEMF produced satisfying therapeutic effects on fresh and nonunion fractures and osteoporosis [14], [17].…”
Section: Discussionmentioning
confidence: 99%
“…Basically, the three most common EMF application modalities well documented thus far include PEMF, static magnetic fields (SMF) and rotating magnetic fields (RMF). A large body of evidence has shown that PEMF displayed strong osteogenic potential both experimentally and clinically [15], [16], [17], [18], which was primarily associated with the induction of electric currents in tissues to initiate a battery of biological cascades. Several investigators also reported that SMF exposure was able to stimulate in vivo skeletal anabolic responses and increase BMD [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has reported that the cellular functions of bone marrow stromal cell [13], osteoblast [14,15], and osteoclast [16,17] are abnormal under diabetic conditions. Recent study has shown that PEMFs can partially prevent deterioration of bone strength and architecture in streptozotocin (STZ)-induced diabetic rats [18]. However, the precise mechanisms accounting for these favorable biological responses are unclear.…”
Section: Introductionmentioning
confidence: 98%